Early Surgical Management and Outcome in Neural Tube Defects: Experience of A Tertiary Care Paediatric Hospital - Hossain, Md Delwar; Ferdous, KM Noor ul (Dhaka Shishu (Children) Hospital Journal, 2026)
Background: Neural tube defects (NTDs) are significant congenital anomalies resulting from improper closure of the embryonic neural tube, with substantial morbidity and mortality. Timely surgical intervention is crucial in minimizing complications and improving functional outcomes, particularly in low-resource settings. Objectives: This study aims to evaluate the outcome of early surgery in neonates and infants with NTDs and identify postoperative complications. Methods: This prospective observational study was conducted at the Department of Paediatric Neurosurgery, Bangladesh Shishu Hospital & Institute, Dhaka, Bangladesh, from July 2020 to December 2023. A total of 385 neonates and infants with confirmed NTDs (myelomeningocele, meningocele, encephalocele) who underwent surgical repair were enrolled. Data on demographics, clinical features, surgical timing, complications, and functional outcomes were collected and analyzed using SPSS version 26. Logistic regression was used to identify risk factors for complications. Results: Myelomeningocele was the most prevalent defect (72.99%), followed by lipomyelomeningocele (13.51%), with the majority of lesions located in the lumbosacral region (68.83%). Surgery performed within 7 days of birth significantly reduced complications (12.0%) and mortality (2.1%) compared to delayed intervention. Wound infection (33.65%) and new-onset hydrocephalus (25%) were common complications. Delayed surgery, hydrocephalus, and thoracic/cervical lesion location were significant risk factors. At one-year follow-up, 44.94% could walk independently, while 66.75% had neurogenic bladder/bowel dysfunction. Conclusion: Early surgical management of NTDs markedly improves outcomes. Delayed intervention and associated anomalies increase the risk of complications. Strengthening prenatal diagnosis and prompt neurosurgical referral is essential in reducing the long-term burden of NTDs. DS (Child) H J 2024; 40(1): 18-24